ANALISA PENINGKATAN KUALITAS PADA PELAYANAN JASA PT. SUCOFINDO ANALYTICAL LABORATORIUM SURABAYA DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN POTENTIAL GAIN IN CUSTOMER VALUE (PGCV) - Affiudin, Farid; Sulistyawati, Lisa (Jurnal Bisnis Indonesia, 2019)
Customer satisfaction is comparison between customer's expected performance and actual performance. When actual performance is higher than customer expectation, customer will be satisfied and vice versa. Case at service companies, customer satisfaction is one of the important factor in creating good climate for business, in this case study, PT Sucofindo Analytical Laboratory Surabaya has not maximized in serving customer needs. Therefore, it needs to be analyzed the factors affecting that matter. From the quality service and the application of marketing mix, consist of Reliability, Responsiveness, Assurance, Empathy, Tangible, at PT Sucofindo Analytical Laboratory Surabaya which have been analyzed by using Importance Performance Analysis from twenty one attributes which represent the five variables show there are five things to be improved. The gap analysis between actual performance and expectation shows that performance of PT Sucofindo Analytical Laboratory Surabaya has not surpassed customer expectations. Keywords  : service quality, marketing  mix  applications,  importance performance analysis (IPA),potential gain in customer value (PGCV)  customer satisfaction